Renaissance and religion: the Bible in a time of radical change - P. G. R. de Villiers (Acta Theologica)
This article investigates how perspectives on religion in Renaissance thought affected their interpretation of the Bible. After a first section on the relevance of seminal characteristics and the social context of the Renaissance to this topic, three approaches to religion by Renaissance authors are outlined. In each of the discussions of these approaches, remarks about the implications of these views for the role and interpretation of the Bible are offered.